2019
DOI: 10.1136/bcr-2019-229948
|View full text |Cite
|
Sign up to set email alerts
|

Unusual pseudocyst in a wandering spleen

Abstract: Pseudocysts of the spleen are rare, generally asymptomatic lesions developing secondary to trauma, infection or infarction. When symptomatic, they typically present as non-specific pain in the left hypochondrium, with or without a palpable lump on clinical examination. However, these conventions fail when they occur in a wandering spleen, making imaging critically important. This report describes an unusual case of a 50-year-old who presented with a large cystic mass in a pelvic spleen; imaging facilitated a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The wandering spleen with a large cyst was located in the left lower quadrant of abdomen and there was fluid collection in the peritoneal cavity epithelial lining in utero during the perinatal period, which progresses to epithelial cysts and may coexist with abnormal development of ligaments leading to the congenital wandering spleen. 6,7,9,10,12 History taking and physical examination are the primary tools for making an initial impression. Some patients may be asymptomatic or complain of mild intermittent pain because splenic congestion varies with intermittent torsion and spontaneous detorsion.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The wandering spleen with a large cyst was located in the left lower quadrant of abdomen and there was fluid collection in the peritoneal cavity epithelial lining in utero during the perinatal period, which progresses to epithelial cysts and may coexist with abnormal development of ligaments leading to the congenital wandering spleen. 6,7,9,10,12 History taking and physical examination are the primary tools for making an initial impression. Some patients may be asymptomatic or complain of mild intermittent pain because splenic congestion varies with intermittent torsion and spontaneous detorsion.…”
Section: Discussionmentioning
confidence: 99%
“… 4–10 But only 5 cases among them had the wandering spleen with splenic true cyst 4–8 . Manoharan et al reported a wandering spleen with a cyst, but the cyst was a pseudocyst 9 . And Nawaz et al also reported a wandering spleen with a cyst in a neonate, and they did partial splenectomy and splenopexy 10 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations